2018
DOI: 10.4236/ajps.2018.91001
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Potential of Seeds of Perennial Soybean cv. Comum Coated with Different Materials

Abstract: The aim of this study was to evaluate the effect of different seed coatings on the physiological potential of perennial soybean cv. Comum. The following treatments were tested: control (no coating); limestone + polyvinyl acetate (PVA); limestone + sand + PVA; limestone + charcoal + PVA; calcium silicate + PVA; calcium silicate + sand + PVA; and calcium silicate + charcoal + PVA. Seeds were evaluated for water content (WC), maximum diameter (MAD), minimum diameter (MID), 1000-seed weight (TSW), germination test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…We found that N. wightii provided the highest values for soil quality index (Jain et al 2018). In our plots, we observed that N. wightii developed a very dense perennial root system during the six years of our experiment, in addition this plant species showed an extraordinary regrowth capacity (Xavier and Vieira et al 2018). These factors make the species more advantageous, re ecting in a high soil quality index.…”
Section: Discussionsupporting
confidence: 49%
“…We found that N. wightii provided the highest values for soil quality index (Jain et al 2018). In our plots, we observed that N. wightii developed a very dense perennial root system during the six years of our experiment, in addition this plant species showed an extraordinary regrowth capacity (Xavier and Vieira et al 2018). These factors make the species more advantageous, re ecting in a high soil quality index.…”
Section: Discussionsupporting
confidence: 49%
“…GroundEye ® was efficient in determining the maximum and minimum diameters of coated Stylosanthes sp. and perennial-soybean seeds in the studies of Acha et al (2016), Silva et al (2017), Acha et al (2018) and Xavier and Vieira (2018). These authors obtained significant increases for those variables with the different coating methodologies Table 3.…”
Section: Resultsmentioning
confidence: 85%
“…uneven coating, contamination by other species and coating that reduces seed germination. Divergences may exist between studies on seed coating due to the material used and thickness of the layer deposited on the seeds (Somrat et al, 2018;Xavier and Vieira, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oliveira et al (2003) working with sand and limestone found a decrease in germination percentages of sweet pepper seeds. This delay in germination is a recurring problem in several studies (Silva & Nakagawa, 1998;Tunes et al, 2012;Caldeira et al 2016;Acha et al, 2016;Sousa et al, 2016;Silva et al., 2017;Xavier & Vieira, 2018;Acha et al, 2018). However, in spite of this delay, studies indicate that the process of coating seeds is a great alternative for maintaining their physiological characteristics (Medeiros et al 2004;Brites et al, 2011;Sousa et al, 2017).…”
Section: Resultsmentioning
confidence: 99%